The evolution of weternized political parties and party systems - Barros, Marilene (REVISTA AGON - Ἀγών - ISSN: 2965-422X, 2022)
Political parties are essential to the functioning of democratic politics, as they serve a variety of functions such as structuring the electoral system, representing interests and shaping political identity. Although every nation has their own political and social particularities, it is possible to discern some generalizations about party systems in advanced industrial democracies. The literature reviewed in this essay explores the formation and evolution of party systems in these nations, illuminating the basic approaches to understanding party systems today. Although there are significant differences in the approaches, I argue that they are in many ways complementary to one another, and enable us to draw a complete picture of the forces that shape party systems.